Exploring the Role of Behavioral Finance in Investment Choices of IT and ITES Employees in the Chennai Region - Kavya, J.; Kotteeswaran, M. (Journal of Neonatal Surgery, 2025)
This study investigates the role of behavioral finance in shaping the investment decision-making of IT and ITES professionals in the Chennai region. While conventional financial theories assume rational behavior, emerging evidence suggests that investment decisions are often influenced by cognitive biases and psychological factors. This research adopts a quantitative methodology to examine how six independent variables—Loss Aversion, Herd Behavior, Availability Heuristic, Financial Literacy, Income Level, and Investment Experience—affect the dependent variable, Investment Decision-Making. Data was collected through a structured questionnaire from a stratified random sample of 200 IT and ITES employees in Chennai. Descriptive statistics indicated a financially literate, moderately experienced workforce, with high exposure to behavioral influences. Correlation analysis revealed significant positive relationships between investment decision-making and variables such as financial literacy (r = 0.542) and investment experience (r = 0.489), while loss aversion had a notable negative correlation (r = -0.431). Regression analysis confirmed that financial literacy, experience, and income level are strong predictors of investment decisions (Adjusted R² = 0.569), whereas loss aversion remains a key deterrent. ANOVA results showed significant variation in investment behavior across income and experience groups. The findings highlight that behavioral biases persist even among educated professionals, influencing their ability to make sound financial decisions. The study recommends targeted financial education, behavior-aware advisory services, and workplace investment programs. This research provides critical insights for financial planners, HR professionals, and policymakers, emphasizing the need for integrating behavioral finance principles into personal financial management for urban professionals in India